Water Deficit Effect on the Relationship between Temperature during the Seed Fill Period and Soybean Seed Oil and Protein Concentrations - Carrera, Constanza Soledad (2009)
Since most soybean [Glycine max (L.) Merr.] seed is processed into meal and oil, there is a growing concern about environmental effects on soybean seed composition. The aim of this work was to investigate how water deficit affects the well-known relationship of soybean seed oil and protein concentrations with temperature and, alternatively, with solar radiation during seed fill. We analyzed oil and protein data from multienvironment trials in Argentina (latitude 29° to 38° S). Multiple linear regressions were used to test the effect of water deficit on the relationship between oil, protein, and oil + protein and temperature. The functions relating oil and protein concentrations with average daily mean temperature during seed fill (TmR5R7) changed with water deficit. When precipitation minus potential evapotranspiration during the reproductive period (pp-PETR1R7) was lower than 70 mm, oil increased linearly with increasing TmR5R7 and with rising water deficit. Meanwhile, protein increased linearly with TmR5R7 but decreased linearly with water deficit. Oil + protein concentration held a linear relationship with TmR5R7 even under water deficit. Cumulative solar radiation during seed fill predicts seed quality but shows lower significance than TmR5R7 This research demonstrates that a water-stress indicator (pp-PETR1R7) should be considered in rainfed crops because it affects the well-known relationship of soybean seed oil and protein concentrations with temperature.